A STUDY ON THE ABILITY OF THE EIGHTH GRADE STUDENTS OF SMPN 20 PEKANBARU IN COMPREHENDING PROCEDURE TEXTS - Atia Safitri; Supriusman Supriusman; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The aim of this study was to find out the ability of the eighth grade students of SMPN 20 Pekanbaru in comprehending procedure texts. The population of this research was the eighth grade students of SMPN 20 Pekanbaru. There were 30 students who participated in this study. The research instrument was multiple choice questions, which consisted of 30 questions. The test given include 5 components such as: finding main idea, finding factual information, finding generic structure of procedure text, finding meaning of difficult word and finding references. The data were analyzed by classifying them into 5 levels of ability, such as very poor, poor, mediocre, good and excellent. The result showed that the ability of the eighth grade students of SMPN 20 Pekanbaru in comprehending procedure texts was at mediocre level with the mean score was 55.5. Thus, it can be said that the majority of students was able to comprehend procedure texts. Based on the results of the research, it is advised that the students read more procedure texts and practice comprehending procedure texts to enhance their reading comprehension.Key Words: Students’ Ability, Reading Comprehension, Procedure Texts